Compensatory kidney hypertrophy/hyperplasia after nephrectomy in mice: alterations of connexin 43 (Cx43) phosphorylated isoforms - Silva, Priscyla T. D. da; Oloris, Silvia C. S.; Avanzo, Jose L.; Fukumasu, Heidge; Silva, Tereza C. da; Hernandez-Blazquez, Francisco J.; Dagli, Maria L. Z. (Brazilian Journal of Veterinary Pathology, 2008)
Compensatory kidney hypertrophy/hyperplasia leads to several changes in kidney structure and function, as increased glomeruli filtration. The aim of this study was to evaluate connexin 43 in remnant mouse kidneys after unilateral nephrectomy. The right kidney was surgically removed from BALB/c mice. Groups were euthanized at 24, 48 and 72 hours, and at 7 and 30 days. Kidney sections of the reminiscent kidneys were stained with Periodic Acid/Schiff and additional slides were submitted to BrdU and Cx43 immunohistochemistry. The results demonstrated an increase in kidney weight as early as 24 hours through 30 post-nephrectomy. In addition, BrdU positive epithelial cells increased at 24 and 48 hours post-nephrectomy. Cx43 was detected in the cytoplasm and membrane of epithelial cells and vasculature. Taking into consideration the quantity, intensity and localization of Cx43 immunostaining pattern, we observed that nephrectomized mice presented lower Cx43 expression and a cytoplasmic localization after 24 hours, peaking in 48 hours. Furthermore, western blot revealed that during the first 24 and 48 hours after nephrectomy, P0 (unphosphorylated) and P1 (phosphorylated) Cx43 disappeared, and the products of Cx43 degradation were reduced. On the other hand, after 72 hours the P0 and P1 state reappeared and the amount of degraded peptides also increased. Seven and thirty days after nephrectomy, a higher intensity of P0 and P1 state and a lower P2 (hyperphosphorylated) band were observed. In conclusion, our results suggest that Cx43 phosphorylation results in the retention of Cx43 in cytoplasm and its increased degradation during compensatory renal hyperplasia/hypertrophy.